THE PERFORMANCE OF BI-FILTER ON THE PRODUCTION AND DISEASE INCIDENCE OF PRAWN (PENAEUS MONODON FAB.) - Slamet Budi Prayitno (JOURNAL OF COASTAL DEVELOPMENT, 2000)
It has been long known that the most potent factor that influences prawn production was unfavorable environment due to industrial, agriculture and habitat wastes as well as improper application of good husbandry management. This research was designed to study the effect of biological filter on the growth of tiger prawn, water qualilv, and disease incidence. 7`wo sets of experiments, namely field stddy and laboratory experiment were conducted . Field survey was carrted out to collect field data on actual husbandry practices, production, water and soil quality. Laboratory experiment was aimed at evaluating the efhctiveness of biologicalfilter and disease incidence. Juvenile prawn e (j 5 gr.) at a density of 15 animals/M2; 20 animals/M2, and 25 animals/M2 were used as experimental animals. The observed parameters were field productivity, growth, survival rate, water quolitv, bacterial counts, soil quality and disease incidence. Experiments were carried in 3 replicates. Field survey showed that prawn production decreased steephr at the third production cycle as low as 627.65 kg/Ha compared to the first cycle (1893. 28 kg/lla. Most prawn were weak, and very vulnerable to diseases. Bacterial count was more than I0Jcfii/ml. Water quality rapidly declined as prawn grew especially during the second and third cycles. Laboratory experiment with biologicalfilter in contrast demonstrated better water quality and healthier prawn,. although water quality declined slightly along with both the age and density. The growth rate was better than during field trials; among three treatments there were signdicant dyferences; the survival rate was best at density of I 5 animals/M2 but, the best estimated production was reached by density of 20 animals/M2 producing 2645 kg/Ha/cycle without any problems for around 4 cycles. Disease incidence and parasites infestation was undetected in the tank during the experiment.